(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The contemporary management landscape is increasingly defined not just by strategic planning or operational efficiency but by the ability to understand and manage human behavior in the organizational context. This article explores the socio-psychological characteristics that shape the organization of management processes. It delves into emotional intelligence, leadership behavior, team dynamics, motivational factors, communication systems, and organizational culture as essential psychological and social components. Drawing upon global research and empirical findings, the paper presents a multidimensional approach to management that integrates psychological science and human-centric practices. Findings suggest that aligning socio-psychological principles with organizational objectives results in more adaptive, innovative, and sustainable institutions.